Cultura e poder na organização hospitalar: as relações de poder na implantação da EBSERH em um hospital universitário - Flausino, Vinícius Silva (2015)
Health is a people\'s right and a State obligation, but its promotion is hampered by matters such as resources scarcity and general management issues. The Brazilian federal universities hospitals are central to health promotion system, but, according to Union Account Supreme Court House, they\'re running in crisis. Then, the Federal Government has established the Brazilian Hospital pertaining Services Enterprise (EBSERH), which the declared goal was to promote the recovering of that hospitals and other health organizations. Taking into account the outcomes expected from this new hospital management, and the various individual\'s interests, this study aims to analyze the power relations between the subjects which were involved to the process of implanting the EBSERH at Clinics Hospital (HC) of Triângulo Mineiro Federal University (UFTM), by the light of Foucauldian\'s power approach. It was carried a qualitative research, which methods are social reality interpretation alike (NEVES, 1996; BAUER; GASKELL; ALLUM, 2002). The ethnographic research method, which seeks to understand the individuals in their own environment, considering their behavior, interactions and beliefs trough time and space, was applied. To collect the empirical data, it was carried a documental research, 95 hours of participant examination in different spaces at the organization, and narrative interviews (JOVCHELOVITCH; BAUER, 2002) with 25 interviewees. To analyze the empirical data, it was runned the speech analyze technique (GILL, 2002). The results shown that, in UFTM\'s HC, the power was exercised by many individual parts, which negotiate and renegotiate their realities as from the identity, roles and territories definition. The scarcity of resources and the lack of any options to finance UFTM\'s Hospital were mandatory for its adhesion to EBSERH, which, at the time of the study, wasn\'t able to provide the growth of employee number, raising doubts about its effectiveness in solving the problems that vindication its institution. The concordance or discordance to adhesion to EBSERH separate employees into two different subcultures, characterized by the delineation of dissimilar temporalities discourses. The main basis to power be put in practice were the organizational hierarchy, the professional category and the kinds of employee hiring. The possible combination of each one of the basis put individuals into superior or inferior power position in organization power structure, similarly to the Indian Caste System. The basis were combined to legitimacy promotion discourses, characterized as strategies to exercise power, such as consumption goods scarcity; the \"patient\'s welfare\"; the love to organization; and the occupation of the future by the organizational discourse. The strategies are alike beliefs of Hinduism, such as Karma and Dharma. The power relations analyzed and its implications must be challenged, or healthcare services improve will not be achieved.